A case of 25 gauge vitrectomy for malignant glaucoma with microphthalmos - Nakajima M (Dove Medical Press, 2013)
Masami Nakajima, Yusuke Hara, Yoshio Yamazaki Department of Ophthalmology, Division of Visual Science, Nihon University School of Medicine, Tokyo, Japan Abstract: We report the first case report of pars plana lensectomy (PPL) and pars plana vitrectomy using a 25 gauge vitrectomy system for microphthalmos. Results: A 45-year-old woman reported repeated pain in her left eye, despite the use of medications. Ultrasound biomicroscopy revealed a narrow angle and thickened sclera. The lens and the iris showed anterior displacement with a flattening of the ciliary body. The axial length was 15.16 mm in the right eye and 15.04 mm in the left eye. She was diagnosed with a malignant glaucoma with microphthalmos. The patient underwent PPL and pars plana vitrectomy, using a 25 gauge vitrectomy system. The intraocular pressure was well controlled after surgery without medication. Conclusion: We considered the PPL and 25 gauge vitrectomy effective in microphthalmos when performed safely. Keywords: microphthalmos, aqueous misdirection, malignant glaucoma, ultrasound biomicroscopy, 25 gauge vitrectomy